Information needs of small ruminant rearers in peri-urban areas of Southwest Nigeria (2010)
The study aimed at recognizing the information needs of small ruminant rearers within households in three peri-urban areas of Oyo state and Ile-Ogbo in Osun state. The respondents were purposively selected and snowball technique was used to identify them. Focus group discussion and questionnaire/interview schedule were used to collect information for the study. It was discovered that 51.3% of respondents were aged 50years and above indicating that the rearing of small ruminants was also suitable for the more settled and slower citizens and that 73.6% of the respondent had some form of education. Majority of the respondents (87.6%) earned less than N5,000.00 monthly from small ruminants and 94.2% of them think rearing small ruminants is profitable. In addition, 77.7% of them reared small ruminants primarily for income generation. The study also revealed that the most important constraints to small ruminant production were theft, death from vehicles and pests and disease infestations and that the respondents needed information on small ruminant rearing in areas like feeding, management System, housing, disease Identification and record keeping.